PERANGKAT PEMBELAJARAN FISIKA BERBASIS MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DENGAN PENDEKATAN GUIDE INQUIRY PADA MATERI FLUIDA DINAMIS TERINTEGRASI BENCANA ANGIN TOPAN - Retno Riyaningtyas; Yulkifli Yulkifli; Ahmad Fauzi (PAKAR Pendidikan, 2016)
This research is motivated importance of community preparedness to face the threat of hurricanes. This research aims to develop devices based learning high school physics teaching model of problem based learning with guided inquiry approach to the material dynamically integrated fluid cyclone with valid criteria, practical and effective. This type of research is a research-development using a model 4-D comprising the steps define, design, develop and dessiminate. In the define phase-end preliminary analysis, the analysis of the students, the task analysis, material analysis and the analysis of learning goals. At the design stage to do the preparation beracuan test criteria, the selection of media, format selection and initial design learning device. On Stage develop expert assessment (validation) and test development (practicalities and effectiveness) learning device. Data were analyzed using descriptive percentages. Results of the research is already successfully developed a learning tool in the form of high school physics syllabus, lesson plans, modules and assessments on integrated dynamic fluid material cyclone with very valid category with a percentage of 94.52%, very practical with a percentage of 88.91% and effectively with the percentage of 78 , 52%.